1998
DOI: 10.1212/wnl.50.1.2-a
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the localization of brain prion proteins during scrapie infection

Abstract: Prion proteins (PrP) were localized in the brains of normal and scrapie-infected hamsters by immunohistochemistry and Western blotting. PrP monoclonal antibodies and monospecific anti-PrP peptide sera, which react with both the cellular (PrPC) and scrapie (PrPSc) isoforms of the prion protein, were used to locate PrP in tissue sections. In normal hamsters, PrPC was located primarily in nerve cell bodies throughout the CNS; whereas, in the terminal stages of scrapie, PrP immunoreactivity was shifted to the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…Earlier studies showed that some PrP Sc is released from degenerating neurons and their processes into the extracellular space of the CNS, where it accumulates in perivascular, subpial, and subependymal spaces (38,39), and is taken up by activated microglia and reactive astrocytes (5,37). Additionally, histoblots indicate that a substantial portion of the residual thalamic PrP Sc is located in large bundles of axons within or immediately adjacent to the thalamus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that some PrP Sc is released from degenerating neurons and their processes into the extracellular space of the CNS, where it accumulates in perivascular, subpial, and subependymal spaces (38,39), and is taken up by activated microglia and reactive astrocytes (5,37). Additionally, histoblots indicate that a substantial portion of the residual thalamic PrP Sc is located in large bundles of axons within or immediately adjacent to the thalamus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because astrocytic gliosis marked by the deposition of fibrils composed of GFAP is a prominent feature of prion disease (DeArmond et al 1987;Hwang et al 2009), we investigated whether GFAP might be used as a surrogate marker for prions. To interrogate this posit, we inoculated prions into Tg mice expressing luciferase (luc) under the GFAP gene (Gfap) promoter, denoted Tg(Gfap-luc) mice (Tamgüney et al 2009a).…”
Section: Bioluminescence Imagingmentioning
confidence: 99%
“…Sometimes PrP accumulations appear in the form of plaques. 6,7 Based on previous studies carried out in various animals, and knowing that extrapolation is legitimate, a retrograde spread of modified prion proteins from the zone of entry into the nervous system is proposed here. For some authors, such transmission is anterograde; 8 others see it as retrograde [9][10][11] and still others posit a mixed form.…”
Section: Introductionmentioning
confidence: 99%